Structure-activity relationship of PET-degrading cutinase regulated by weak Ca2+ binding and temperature - Fumiya Kondo; Narutoshi Kamiya; Gert-Jan Bekker; Satoshi Nagao; Nobutaka Numoto; Hiroshi Sekiguchi; Nobutoshi Ito; Masayuki Oda (Biophysics and Physicobiology)
Enzyme function is often regulated by weak metal-ion binding, which results from conformational changes while maintaining conformational fluctuations. We analyzed the structure and function of cutinase-like enzyme, Cut190, using biophysical methods such as X-ray crystallography and molecular dynamics (MD) simulations, showing that its structure and function are finely regulated by weak Ca2+ binding and release. We succeeded to stabilize the enzyme by introducing a disulfide-bond which can degrade polyethylene terephthalate (PET) to PET monomers at the glass transition temperature of PET, ≈70°C. In this study, using the stabilized Cut190 mutants, Cut190**SS and Cut190**SS_F77L, we evaluated the requirement of Ca2+ for catalytic activity at 70°C, showing that the enzyme expressed the activity even in the absence of Ca2+, in contrast to that at 37°C. These results were supported by multicanonical MD analysis, which showed that the respective forms of the enzyme, such as closed, open, and engaged forms, were exchangeable, possibly because the potential energy barriers between the respective forms were lowered. Taken together, the conformational equilibrium to express the catalytic activity was regulated by weak Ca2+ binding at 37°C, and was also regulated by increasing temperature. The respective conformational states of Cut190**SS and Cut190**SS_F77L correlated well with their different catalytic activities for PET.